Model-driven engineering and software development : 5th International Conference, MODELSWARD 2017, Porto, Portugal, February 19-21, 2017, Revised selected papers /: 5th International Conference, MODELSWARD 2017, Porto, Portugal, February 19-21, 2017, Revised selected papers. (2018) - Unknown
No abstract available